2022
DOI: 10.3389/fonc.2022.1013035
|View full text |Cite
|
Sign up to set email alerts
|

ENO1 contributes to 5-fluorouracil resistance in colorectal cancer cells via EMT pathway

Abstract: IntroductionChemoresistance is a major barrier in the treatment of colorectal cancer (CRC) and many other cancers. ENO1 has been associated with various biological characteristics of CRC. This study aimed to investigate the function of ENO1 in regulating 5-Fluorouracil (5-FU) resistance in CRC.MethodsENO1 level in 120 pairs of tumor tissues and adjacent normal tissues was examined by immunohistochemistry, and the correlation between ENO1 expression and prognosis was explored by survival analysis. Its role and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…Interestingly, by single-cell sequencing data analysis of CD8 + T cells, we found that ENO1 and inhibitory receptors such as LAG3 were upregulated with the progression of CD8 + T-cell exhaustion in our study, which was consistent with the results of L.F. Gemta's study and suggested that ENO1 may undergo posttranslational modi cation in exhausted CD8 + T cells [17,47]. ENO1 can, through the regulation of the cell cycle[48] and apoptosis, maintain cancer cell proliferation and resistance to cell death [49], and through the induction of EMT, promote invasion and metastasis [50].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, by single-cell sequencing data analysis of CD8 + T cells, we found that ENO1 and inhibitory receptors such as LAG3 were upregulated with the progression of CD8 + T-cell exhaustion in our study, which was consistent with the results of L.F. Gemta's study and suggested that ENO1 may undergo posttranslational modi cation in exhausted CD8 + T cells [17,47]. ENO1 can, through the regulation of the cell cycle[48] and apoptosis, maintain cancer cell proliferation and resistance to cell death [49], and through the induction of EMT, promote invasion and metastasis [50].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to its role as a glycolytic enzyme, α-enolase (ENO1), the most extensively studied isoform of ENO, is expressed on the cell surface of most tumors and has been shown to be an oncogenic factor in multiple cancers that depends on the modulation of a variety of biological events, such as glycolysis, angiogenesis, invasion and metastasis (10,11). In particular, interference with ENO1 has been shown to decrease glycolysis, cell growth, metastasis and chemotherapy resistance in CRC (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%